Is tissue polypeptide antigen more accurate than serum CEA for diagnosing pancreatic cancer?. Issue 1 (January 1986) - Panucci, A; Fabris, C; Del Favero, G; Basso, D; Di Mario, F; Marchioro, L; Piccoli, A; Lise, M; Burlina, A; Naccarato, R
Abstract : Tissue polypeptide antigen (TPA) and carcinoembryonic antigen (CEA) were determined in the sera of 36 control subjects, 30 patients with pancreatic cancer, 35 with chronic pancreatitis and 25 with non-pancreatic digestive disease to evaluate their role in detecting pancreatic malignancy. Abnormal values of TPA and CEA were found in 28 and 19 of 30 patients with pancreatic cancer, and in four and seven of 35 patients with chronic pancreatitis, respectively. Raised titres of TPA were observed more often than equivalent serum CEA in simulated pancreatic diseases. The receiver-operating (ROC) characteristic curves showed that TPA was more discriminating than CEA in detecting pancreatic cancer. Specificity was enhanced when both titres were abnormally high and sensitivity when one titre was raised, but the diagnostic accuracy of TPA alone has not improved, which satisfactorily discriminates pancreatic cancer from chronic pancreatitis.